Competence of Arabic Language Learning Media Lecturers in the Perspective of the Australian Federation of Modern Language Teachers Associations (AFMLTA) - Putra, Wahyu Hanafi; Isnaini, Rohmatun Lukluk; Yousry, Islam (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
The purpose of the study was to describe the competence of INSURI Ponorogo Arabic learning media lecturers with a standard perspective and teacher professionalism, according to The Australian Federation of Modern Language Teachers Associations (AFMLTA). This research is qualitative and uses a case study approach. Carried out in the INSURI Arabic language education study program. Research data in the form of competence and professionalism of PBA Learning Media lecturers are limited to projections of student receptive ability development through Arabic cartoons accessed from Marhaban Academy Channel on the https://www.youtube.com/@MarhabanAcademy link. The sources of research data are lecturers, students, and learning activities in the classroom. Data collection techniques are carried out by observation, interviews, and documentation. The analysis of research data is carried out by reducing data, presenting data, and drawing conclusions. The results showed, referring to the standards of AFMLTA foreign language teachers. Lecturers of Arabic learning media courses have met AFMLTA standards, namely mastering pedagogic, professional, and social competencies. Pedagogic competence is colored by the ability to manage classes. Professional competence is aimed at the formulation of learning objectives before lecturers step into the learning process. Meanwhile, social competence is aimed at creating a learning atmosphere by adjusting the curriculum and culture of the INSURI Ponorogo campus. Thus, the existence of AFMLTA can measure the competence and professionalism of language teachers outside Australian countries.